Nano-Innovations for a Greener Future- Merging Chemistry and Sustainability - Dua, Meenu; Sharma, Nandini; Vaishali, Vaishali (Journal of Neonatal Surgery, 2025)
Precision agriculture offers an effective way to lower farming costs while boosting crop yields, addressing many challenges faced in conventional farming. Innovative techniques are now available to improve these practices, with nanotechnology playing a key role. By enabling control at the nanoscale, nanotechnology allows for highly accurate interventions. For example, certain nanoparticles can be designed to reduce damage to non-target plant tissues, aiding in early disease detection and treatment. It also enhances the ability of plants to absorb nutrients. When properly applied, machine-driven biological nanotechnology has the potential to transform agricultural systems. By targeting specific nanoparticles that can minimize damage to no target plant, nanotechnology can be used for disease detection and treatment, as well as increasing plant nutrient enhancement ability. Active ingredients with a nano size can have a higher efficiency and penetration. Nanotechnology can significantly enhance precision farming by enabling more accurate, efficient, and sustainable agricultural practices. Nanotechnology can be used in precision farming in various ways, nanoparticles can carry fertilizers, pesticides, or herbicides directly to specific plant parts or affected areas. This reduces waste, minimizes environmental impact and also the nano sensors can detect soil conditions, plant health, moisture levels, and disease presence in real time. This data helps farmers make precise decisions about irrigation, fertilization, and pest control. Not only this but Seeds coated with nanomaterials can have improved germination rates, controlled nutrient release, and better resistance to environmental stress. This book chapter aims to determine the use of nano chemistry in sustainability of agriculture and precision farming.